(untitled) - Hill, Christian (New York, 2015)
The second edition features a new chapter on data analysis with the pandas library and comprehensive updates, and new exercises and examples. A final chapter introduces more advanced topics such as floating-point precision and algorithm stability, and extensive online resources support further study. This textbook represents a targeted package for students requiring a solid foundation in Python programming
Lập trình trong vật lý tính toán
Keywords: Science,Khoa học,Python (Computer program language),Python (Ngôn ngữ chương trình máy tính); Data processing.,Xử lý dữ liệu